Pengembangan Media Pembelajaran Finger Painting Terhadap Kreativitas Bermain Anak Usia 5-6 Tahun Di TK Cerdas Ceria Kecamatan Sipoholon (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The purpose of this research is to create a finger painting poster learning media to enhance the creativity of 5-6-year-old children at TK Cerdas Ceria in the Sipoholon District. The research methodology used in this study is the Research and Development (R&D) approach. The development process follows the Borg & Gall procedure, which consists of ten main stages; however, the researcher only focuses on seven stages in this research. Data collection involves the use of questionnaires given to media experts, language experts, and early childhood experts. To assess the quality of the finger painting poster learning media, a student response questionnaire is conducted. The collected data is qualitative and analyzed using assessment criteria guidelines to evaluate the developed finger painting poster learning media's quality. The result of this research is the finger painting poster learning media product designed to enhance children's creativity during play. After validation by experts, the final product is proven to meet the appropriate criteria, with an average score of 97% from media experts, 95% from language experts, 93% from early childhood experts, and 97% from the small test group. The finger painting poster media is considered suitable for use as a learning medium.